Grounding after moderate eccentric contractions reduces muscle damage - Brown, R.; Chevalier, G.; Hill, M. (Open Access Journal of Sports Medicine, 2015)
Grounding a human to the earth has resulted in changes in the physiology of the body. A pilot study on grounding and eccentric contractions demonstrated shortened duration of pain, reduced creatine kinase (CK), and differences in blood parameters. This follow-up study was conducted to investigate the effects of grounding after moderate eccentric contractions on pain, CK, and complete blood counts. Thirty-two healthy young men were randomly divided into grounded (n=16) and sham-grounded (n=16) groups. On days 1 through 4, visual analog scale for pain evaluations and blood draws were accomplished. On day 1, the participants performed eccentric contractions of 200 half-knee bends. They were then grounded or sham-grounded to the earth for 4 hours on days 1 and 2. Both groups experienced pain on all posttest days. On day 2, the sham-grounded group experienced significant CK increase (P<0.01) while the CK of the grounded group did not increase significantly; the between-group difference was significant (P=0.04). There was also an increase in the neutrophils of the grounded group on day 3 (P=0.05) compared to the sham-grounded group. There was a significant increase in platelets in the grounded group on days 2 through 4. Grounding produced changes in CK and complete blood counts that were not shared by the sham-grounded group. Grounding significantly reduced the loss of CK from the injured muscles indicating reduced muscle damage. These results warrant further study on the effects of earthing on delayed onset muscle damage.